EVALUASI PROGRAM KERJA PENGAWAS SD/MI DI UPT CURUP KABUPATEN REJANG LEBONG PROPINSI BENGKULU - Wiwin Arbaini Wahyuningsih (Manajer Pendididikan, 2017)
This study aims to determine the level of achievement of the objectives of the program supervisor SD/M in the Education Department Rejang Lebong I. This study is the evaluation of the model Goal Oriented Approach By Ralph Winfred Tyler. The results of that study; the achievement of program goals still need to be improved both the supervisors, teachers, and the Department of Education; many supervisors do not meet the qualification standards PERMENPAN No. 14 of 2016 on school superintendent; unavailability of facilities and infrastructure to support the regulatory tasks; the ability of supervisors draw up programs and monitoring reports either category; intensity control is not optimal target schools.